1993
DOI: 10.1063/1.465371
|View full text |Cite
|
Sign up to set email alerts
|

The low lying electronic states of O−3

Abstract: The energies of the three lowest lying excited states of the ozonide anion (1 2B2, 1 2A1, 1 2A2) at the optimized geometry of the X 2B1 ground state are theoretically predicted at the MRCI-SD level of theory using large atomic natural basis sets. The calculated vertical excitation energy Tv=2.85 eV for the 1 2A2←X 2B1 transition, which has a large transition moment, is in good agreement with the experimental results for the isolated O3− anion in host matrices and solution between 2.69–2.81 eV. The state symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…As expected from the calibration studies and former experience [8,9,11], the theoretically determined adiabatic electron affinities of Sz (see Table VI) are below the experimental result: The MRCI+Q results with the ANO3 basis amounts to 1.48 eV, with an important contribution of 0.19 from the size-consistency correction. With the ANO2 contraction, which does not include g-type basis functions, the computed MRCI+Q electron affinity is smaller by 0.06 eV, indicating that, similar to the S atom, the employed basis sets are not yet saturated for the higher-angular-momentum components.…”
Section: Electron Afbnity Of S2mentioning
confidence: 48%
See 1 more Smart Citation
“…As expected from the calibration studies and former experience [8,9,11], the theoretically determined adiabatic electron affinities of Sz (see Table VI) are below the experimental result: The MRCI+Q results with the ANO3 basis amounts to 1.48 eV, with an important contribution of 0.19 from the size-consistency correction. With the ANO2 contraction, which does not include g-type basis functions, the computed MRCI+Q electron affinity is smaller by 0.06 eV, indicating that, similar to the S atom, the employed basis sets are not yet saturated for the higher-angular-momentum components.…”
Section: Electron Afbnity Of S2mentioning
confidence: 48%
“…In the assignment and interpretation of some of the spectroscopic data quantumchemical calculations have proved to be useful. As examples we mention studies on the low-lying electronic states of 02 [7], 03 [8], and S3 [9], which gave information on potential-energy surfaces, transition energies, and spectral intensities. An additional challenge connected with these investigations was the accurate calculation of electron affinities [10], which still remains one of the open problems for highly accurate calculations on atoms, diatomic, and small polyatomic molecules [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies 51,59,62,64,65 have shown that nondynamical correlation alone is not sufficient for a quantitative description of the excitation energies of ozone. In these studies, dynamical correlation is included in the multiconfigurational treatment of the wave function by means of perturbation theory (CASPT2 level), 59 configuration-interaction (MRCI level), 51,64,65 or the EOM-CCSDT formalism. 62 In the present work, dynamical correlation has been added using the SplitGAS method.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…2 As such, numerous experimental and theoretical efforts have focused on characterizing the photochemistry of O 3 − in both gaseous [3][4][5][6][7][8] and aqueous 9, 10 environments. Recently, the interactions of ozonide with water and other species important in the troposphere have been implicated in models as a possibly significant contributor to ion-induced nucleation leading to the formation of atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%